(untitled) (Archaeologia Adriatica, 2013)
The article deals with the level of understanding of settlement wholes in the Neolithic in the eastern Adriatic region. It offers a comparison of the results of earlier and recent research as well as analysis of modest understanding of settlement aspects from the earlier excavations. The author concludes that the main reason for such situation can be found in the research strategy with primary orientation to the vertical dimension and small research areas indicating that it is necessary to change research strategies and orient to horizontal dimension of a site.